2020
DOI: 10.1364/ol.391834
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural network inversion for 3D laser absorption imaging of methane in reacting flows

Abstract: Mid-infrared laser absorption imaging of methane in flames is performed with a learning-based approach to the limited view-angle inversion problem. A deep neural network is trained with superimposed Gaussian field distributions of spectral absorption coefficients, and the prediction capability is compared to linear tomography methods at a varying number of view angles for simulated fields representative of a flame pair. Experimental 3D imaging is demonstrated on a methane–oxygen laminar flame doublet ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In this work, we adopt X min = 0.01, X max = 0.12, T min = 318 K, and T max = 1300 K. The dataset is generated with 19 Subsequently, path integrated absorbance for the j th beam in the training and validation sets is standardized. The process of standardization has two benefits.…”
Section: A Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we adopt X min = 0.01, X max = 0.12, T min = 318 K, and T max = 1300 K. The dataset is generated with 19 Subsequently, path integrated absorbance for the j th beam in the training and validation sets is standardized. The process of standardization has two benefits.…”
Section: A Datasetmentioning
confidence: 99%
“…Previous work employed CNNs in CST and showed that their models could achieve a similar accuracy level as simulated annealing [17] and the reduction in network parameters [18]. In addition, CNN has been applied in a proofof-concept experiment to reconstruct the 3-D distribution of methane concentration using mid-infrared CST [19]. Although these endeavors are promising for the industrial application of CNN in CST, the following three issues remain to be addressed as a matter of urgency.…”
Section: Introductionmentioning
confidence: 99%
“…Convolutional neural nets (CNNs) have been particularly successful in the realm of image processing and were therefore adapted for tomographic reconstruction by numerous groups. For instance, Huang et al [27], [28], [29] conducted 2D laser absorption tomography and 3D chemiluminescence tomography via CNNs, and Wei et al [30], [31] used CNNs to reconstruct 3D mole fraction and temperature fields from laser absorption measurements of methane and ethylene flame doublets. These examples employed the common supervised training paradigm, in which phantom distributions (c exact ) paired with synthetic measurements (b exact = Ac exact ) are used to train the network.…”
Section: B Deep Learning Reconstruction Algorithmsmentioning
confidence: 99%
“…These examples employed the common supervised training paradigm, in which phantom distributions (c exact ) paired with synthetic measurements (b exact = Ac exact ) are used to train the network. Phantoms for training have been obtained from previous reconstructions [28], [29], random Gaussian fields [27], [30], and large-eddy simulations [31], and random errors were usually added to b train to make the reconstruction procedure robust to noise. While this approach can yield accurate estimates of the QoI when the training set accurately represents the target physics, the application of DNN-based reconstruction to targets that exhibit unique structures is not reliable.…”
Section: B Deep Learning Reconstruction Algorithmsmentioning
confidence: 99%
“…Deep learning, as its extraordinary capability of feature abstracting and non-linear fitting 13 , can potentially deal with the issues mentioned above. Some attempts have been made to adopt deep learning algorithms in some reconstruction tasks like the sliced absorption spectroscopy, and chemiluminescence reconstruction [14][15][16] . However, such end-to-end methods (using the projections as the input and reconstructed object as the outputs) potentially deduct the generalization of the model.…”
mentioning
confidence: 99%